APPLYING THE BUDDHIST PRINCIPLES FOUND IN THE TIROKUDDA SUTTA FOR IMPROVING THE QUALITY OF LIFE OF BUDDHISTS IN CONTEMPORARY SOCIETY - (Thongon), Phramaha Seksak Jantawangso; ., Phrakru Kositwattananukul; Panasree, Sitthichok (Journal of MCU Nakhondhat, 2026)
This research article aims to: 1) Examine concepts and theories regarding quality of life development; 2) Study Buddhist principles appearing in the Tirokudda Sutta; and 3) Apply the Buddhist principles from the Sutta to develop the quality of life of Buddhists in contemporary society. This study employs a qualitative research methodology based on documentary research, analyzing the Pali Canon (Tipitaka), its commentaries (Atthakatha), and contemporary academic literature. The research instruments consist of data recording forms and content analysis frameworks. Data were analyzed using content analysis and logical interpretation. The research findings indicate that: 1) Contemporary concepts of quality of life development focus on four dimensions physical, psychological, social, and intellectual whereas Buddhism emphasizes internal development through the Fourfold Development (Bhavana-4), encompassing the development of body, morality, mind, and wisdom. 2) The core Buddhist principles in the Tirokudda Sutta consist of four main aspects: Gratitude and Mutual Gratefulness (Katannutakatavedita), Moral Shame and Moral Dread (Hiri-Ottappa), the Three Bases of Meritorious Action (Bunyakariyavatthu-3), and the Six Principles of Cordiality (Saraniyadhamma-6). and 3) The key discovery is the synthesis and elevation of these Buddhist principles into a paradigm innovation designated as the HYBRID MODEL (H - Hiri & Ottappa, Y - Yoniso-manasikara, B - Behavioral & Belief Integration, R - Religious Innovation, D - Developmental Wisdom). This model functions as a mechanism to elevate internal conscience, mitigate structural isolation, and harmonize spiritual happiness with the modern scientific framework of The Spiritual D.O.S.E. Model. This body of knowledge can serve as a conceptual framework for developing the quality of life of Buddhists. Furthermore, it offers guidelines for policy formulation, educational management, and social development, demonstrating that Buddhist principles, ethics, and modern innovation can advance together as an effective tool to enhance the quality of life based on intrinsic human values.